EFEKTIFITAS PARACETAMOL SEBAGAI ANTIPIRETIK PADA PASIEN CEDERA OTAK SEDANG DAN PARAH DI SALAH SATU RUMAH SAKIT DI SURABAYA - Nasruhan Arifianto (Journal of Pharmaceutical Care Anwar Medika (J-PhAM), 2022)
Patients with moderate and severe brain injury have increased recently. They were having a lot of complications namely seizures,hyperthermia, pain and several other complications. One of the most common complication in patients with moderate and severebrain injury is acute hyperthermia. Acetaminophen is often used for this case. The study of this clinical observation isto compare the effectiveness of Acetaminophen as an antipyretic in patients with moderate and severe brain injuriesin one of the hospitals in Surabaya. The population of this study was patients with moderate and severe brain injuries in ward in one of the hospitals in Surabayawho obtained paracetamol as the therapy. The study was taken from January to April. We studied 16 patients who had febrile episode, 8 patients with moderate brain injury and 8 patients with severe brain injuryreceived acetaminophen, 8 byaxilla examination. Patient's temperature was measured before and 15, 30 minute, 1,2, 3, 4, 5, 6 hours after drug infusion. This study demonstrates the effectiveness of acetaminophen as anantipyretic in moderate brain injury were significantly different (p = 0.583). The Effectiveness of acetaminophen as antipyretic in severe brain injury does have a significant difference (p = 0.651). Acetaminophen have the antipyretic activity in moderate and severebraininjuryinone of the hospitals in Surabaya.